Kerja Sama Trilateral Indonesia-Malaysia-Filipina di Perairan Sulu sebagai Alternatif Kerja Sama Keamanan Kawasan Maritim (pp. 181-202) - Wishnu Mahendra Wiswayana (JURNAL KEAMANAN NASIONAL, 2023)
Trilateral cooperation between Indonesia, Malaysia and the Philippines in the Sulu Waters is a unique phenomenon in the context of contemporary security studies. The cooperation leads to a regional security architecture that makes relations between the three countries even more intensive. The relationship became close because of the common security threats experienced by the three countries. These threats vary from the threat of terrorism, smuggling, piracy and other transnational crimes. The three countries then formed a joint system to be able to handle these problems, this situation is hereinafter referred to as cooperative security. This research further identifies cooperative security carried out by Indonesia, Malaysia and the Philippines which can be an alternative security architecture in the maritime area. Based on the cooperative security idea put forward by Richard Cohen that there are four rings that are important elements, namely (1) individual security, (2) maintaining peace, (3) mutual protection and (4) actively promoting stability. The four rings are then used to explain the pattern of relations in the context of cooperative security involving Indonesia, Malaysia and the Philippines. This research then uses a qualitative method, with a descriptive approach to explain the whole process that occurs.